Penerapan Metode Induktif Kata Bergambar untuk Meningkatkan Keterampilan Membaca Permulaan Siswa Kelas 1 SD Inpres Bere-Bere Kecil Kabupaten Pulau Morotai - Julia Ismail; Desli Raraga; Masayu Gay (Peneliti.net, 2021)
This research is a Classroom Action Research (PTK) by Suharmisi Arikunto, (2018) which consists of two cycles. The subjects of this study were 11 students in grade I SD Inpres Bere-bere. There were 11 students consisting of 7 female students and 4 male students. Data collection techniques used tests, observation and documentation. In cycle I learning outcomes, the number of successful students was 4 students (36%) out of a total of 11 students (100%). Meanwhile, 7 students (63%) were not successful. With these results so that researchers conducted research into cycle II, in cycle II there was a significant increase, namely students who managed to become 9 students (81%). The improvement of student learning outcomes from cycle I to cycle II was 45%. The results of this study are due to the use of pictorial word inductive methods that have been effective by the teacher. So that the researcher can conclude that the use of the pictorial word inductive method can improve the learning outcomes of grade I students at SD Inpres Bere-bere Kecil.